Engineering Immunological Tolerance Using Quantum Dots to Tune the Density of Self‐Antigen Display. (3rd April 2017) - Hess, Krystina L.; Oh, Eunkeu; Tostanoski, Lisa H.; Andorko, James I.; Susumu, Kimihiro; Deschamps, Jeffrey R.; Medintz, Igor L.; Jewell, Christopher M.
Abstract : Treatments for autoimmunity—diseases where the immune system mistakenly attacks self‐molecules—are not curative and leave patients immunocompromised. New studies aimed at more specific treatments reveal that development of inflammation or tolerance is influenced by the form in which self‐antigens are presented. Using a mouse model of multiple sclerosis (MS), it is shown for the first time that quantum dots (QDs) can be used to generate immunological tolerance by controlling the density of self‐antigen on QDs. These assemblies display dense arrangements of myelin self‐peptide associated with disease in MS, are uniform in size (<20 nm), and allow direct visualization in immune tissues. Peptide‐QDs rapidly concentrate in draining lymph nodes, colocalizing with macrophages expressing scavenger receptors involved in tolerance. Treatment with peptide‐QDs reduces disease incidence tenfold. Strikingly, the degree of tolerance—and the underlying expansion of regulatory T cells—correlates with the density of myelin molecules presented on QDs. A key discovery is that higher numbers of tolerogenic particles displaying lower levels of self‐peptide are more effective for inducing tolerance than fewer particles each displaying higher densities of peptide. QDs conjugated with self‐antigens can serve as a new platform to induce tolerance, while visualizing QD therapeutics in tolerogenic tissue domains. Abstract : Quantum dots decorated with myelin peptides induce tolerance in a mouse model of multiple sclerosis. These nanoscale constructs rapidly drain to lymph nodes—tissues that coordinate immune function. The degree of tolerance and the expansion of regulatory T cells capable of controlling disease directly correlate to the density of peptide ligand displayed on the quantum dots.